Influencing factors and characterization methods of nanoparticles regulating amyloid aggregation. Issue 17 (19th April 2022) - Li, Lingyi; Liu, Jianhui; Li, Xinyue; Tang, Yuanhan; Shi, Changxin; Zhang, Xin; Cui, Yuming; Wang, Linlin; Xu, Wenlong
Abstract : This review included four factors that may influence the regulation of amyloid aggregation by nanoparticles and the characterization methods used in such studies. Abstract : Human disorders associated with amyloid aggregation, such as Alzheimer's disease and Parkinson's disease, afflict the lives of millions worldwide. When peptides and proteins in the body are converted to amyloids, which have a tendency to aggregate, the toxic oligomers produced during the aggregation process can trigger a range of diseases. Nanoparticles (NPs) have been found to possess surface effects that can modulate the amyloid aggregation process and they have potential application value in the treatment of diseases related to amyloid aggregation and fibrillary tangles. In this review, we discuss recent progress relating to studies of nanoparticles that regulate amyloid aggregation. The review focuses on the factors influencing this regulation, which are important as guidelines for the future design of NPs for the treatment of amyloid aggregation. We describe the characterization methods that have been utilized so far in such studies. This review provides research information and characterization methods for the rational design of NPs, which should result in therapeutic strategies for amyloid diseases.